The Pauline discourse and the representations of Roman Slavery in the First Century a.D.: a case study on the Epistle to Philemon - Borges, Airan dos S.; Santos, Karina D. (Romanitas - Revista de Estudos Grecolatinos, 2017)
The present article has the general objective of presenting the results obtained by the research developed by the Group of Studies in Classical History and History Teaching of the Graduate course of the Federal University of the State of Rio de Janeiro, UNIRIO. In it, we will analyze Pauline discourse and the representations of Roman slavery during the first century A.D. through the study of the Epistle of Philemon. To do so, we will investigate the plots of the text attributed to Paul and the subject of slavery in the ekklesía, from the key character of the epistolary text, namely, the slave Onesimus.
Keywords: Paleochristianity; Pauline Epistles; Philemon; Roman Slavery; Roman Empire